Tort liability for unsafe sidewalk conditions: a comparative study between Colombia and New York city - Paula A. Barreto Cifuentes, Laura C. Gamarra Amaya, Fernanda Navas-Camargo, (Opción, 2020)
The present paper aims to compare two different perspectives of tort liability in the cases of sidewalk accidents which occur in main cities of two different states, given state negligence. A revision of the evolution pursued in both of the legal frameworks is made. i) On the one hand, the approach made in the legal context of the State of New York (United States of America) where after 2003 responsibility was shifted to private owners ii) and on the other the one implemented in Colombia where State is responsible for such a situation. iii) Discussion is centered on revising if any of the two State has overreached its duties, or if instead the new proceeding is serving well their responsibility of citizen protection. Abstract The present paper aims to compare two different perspectives of tort liability in the cases of sidewalk accidents which occur in main cities of two different states, given state negligence. A revision of the evolution pursued in both of the legal frameworks is made. i) On the one hand, the approach made in the legal context of the State of New York (United States of America) where after 2003 responsibility was shifted to private owners ii) and on the other the one implemented in Colombia where State is responsible for such a situation. iii) Discussion is centered on revising if any of the two State has overreached its duties, or if instead the new proceeding is serving well their responsibility of citizen protection